2002
DOI: 10.1177/0957926502013006758
|View full text |Cite
|
Sign up to set email alerts
|

Caring for older people: a gendered practice

Abstract: This article discusses how ethnomethodology and conversation analysis can contribute to the feminist study of caregiving. Interviews with caregivers of older relatives with disabilities were analyzed using a detailed conversation and membership categorization analysis within an ethnomethodological framework. The interviews were treated analytically as interactional encounters, useful to document instances of identity production and moral versions of oneself as a caregiver. The study describes some instances of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…In this study, carers who were children of a hip fracture patient reported that this experience allowed them to enjoy more time with their parent. Our findings suggested that filial responsibility and gender norms play an important role in the decision about who provides care, as found in other studies [6,9,10,12,55,57] though their function and mechanism requires further study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, carers who were children of a hip fracture patient reported that this experience allowed them to enjoy more time with their parent. Our findings suggested that filial responsibility and gender norms play an important role in the decision about who provides care, as found in other studies [6,9,10,12,55,57] though their function and mechanism requires further study.…”
Section: Discussionsupporting
confidence: 83%
“…A family carer is defined as someone who provides unpaid, regular and substantial practical and/or emotional help to another person beyond that required as part of normal everyday life [7]. Care burden has been reported with negative consequences in physical, psychosocial and economic areas [8,9] especially among women [10][11][12], which suggests that gender is an important issue to consider in informal care.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the way gender gets 'done', I have suggested that MCA allows analysts to examine, in the details of talk's organization, how members maintain the common sense knowledge that shapes our gendered world. It provides a 'critical edge' to ethnomethodological work (Baker, 2000;Paoletti, 2002) and allows us to track and make connections between some of the macro concerns of feminism about the societal regulation of gender and everyday experience (Smith, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…For example, caring is defined as a natural female role associated with nurturing, maternal values (Ungerson, 2000;Coston and Kimmel, 2013). This impinges upon female identity, defining feminine subjectivity as well as moral worthiness (Paoletti, 2002). It is also (O'Connor, 1995).…”
Section: Social Influences Upon Subjective Accountsmentioning
confidence: 99%